Application of sustainable agribusiness management concepts: maintaining ecological and economic balance - Tri Waluyo (Journal of Economics and Business (JECOMBI), 2024)
Sustainable agribusiness has become a major focus in response to global challenges related to environmental degradation and economic instability in the agricultural sector. This research aims to examine and apply the concept of sustainable agribusiness management to maintain a balance between ecological and economic aspects in the agricultural context. This research uses a qualitative approach with descriptive methods. The research results show that the application of the concept of sustainable agribusiness management has a significant positive impact on the agricultural sector. Organic farming practices, polyculture, water use efficiency, and wise waste management are successful strategies in reducing negative impacts on the environment. In addition, the use of information and sensor technology, as well as precision technology in dosing inputs such as fertilizers and pesticides, has increased the efficiency of crop production while reducing waste. Empowering farmers through training, participation in decision making, and building fair partnerships in the supply chain also supports economic and social sustainability. Overall, this research provides a strong foundation for improving more sustainable agricultural practices, creating balanced ecological and economic sustainability in the agribusiness sector.